Analisis Faktor Yang Mempengaruhi Pemilihan Kelas Kepesertaan Jaminan Kesehatan Nasional - Rasdi Awal Nur; Ismail AB; Dina Lusiana Setyowati (Faletehan Health Journal, 2018)
At the end of 2004, the government established a law No.40 year 2004 about National Social Insurance System, with one of the program is National Health Insurance (JKN). This program is expected to carried out the financing of public health services in insurance system and becomes a mandatory insurance system. The data from branch of BPJS Kesehatan on Tarakan city showed the highest registered village on BPJS Kesehatan is SeiPancang village north Sebatik district with 1017 people of independent participants. The purpose of this study was to determine the factors that influenced people in SeiPancang village to choose JKN’s membership class. This study used observational study method with cross sectional study design. Population in this study is people in SeiPancang village north Sebatik district who registered as independent participants of BPJS Kesehatan, with a sample of 156 selected respondents from simple random sampling. The data was analyzed using univariate test and bivariate test with chi square. The chi square analysis showed a correlation between income (p value = 0,001) with choices of JKN’s membership class, and no correlation between accessibility (p value = 0,131) and services quality (p value = 0,091) with choices of JKN’s membership class. In this case, it is expected that the health bureau socializes to the public about the benefits and facilities obtained in each JKN participation class and it is expected that the community to choose the JKN membership class is in accordance with the income earned to achieve fair health financing.